A Bulla da Santa Cruzada (Libraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Boletim da Provincia de Macau e Timor (Typographia Mercanitil, 1886)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Novena Dicta da Graca em Honra de S. Francisco Xavier (Typographia da Cruz do Operario, 1886)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeures de Monseieneur L'eveque de Poitiers (H. Oudin, Libraire- Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm

Oeuvres de Monseigneur L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Oeuvres de Monseigneur, L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Oeuvres de Monseigneur, L'eveque de Poitiers (H. Oudin Libraire-Editeur, 1886)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm

Sermons of the Rev. Joseph Farrell (M. H. Gill and Son LTD., 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

A Religiao em Face da Sciencia - Arduin, Abbade Alexis (Libraria Academica, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Catecismo de la doctrina Cristiana - Astete, P. Gaspar (Editorial Saturnino Calleja, S. A, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Bohemia do espirito, por Camillo Castello Branco - Castelo Branco, Camilo (Livraria Civilisação, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover

Les Commentaires Sur La Guerre des Gaules - Cesar (Hachette et Cie, 1886)

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Coleccion de Platicas Dominicales - Claret, Antonio Maria (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Cursus Scripturae Sacrae, Historica et Critica Introductio - Cornely, Rudolphus (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Coleccion de Platicas dominicales - D. Antonio Maria Claret Y Clara (Liberia Religiosa, 1886)
Stamp of St. Joseph Seminary
Keywords: Good

Platicas Morales para Todos los Domingos Del Ano - D. Ramon Lastiesas (Libreria Religiosa, 1886)
stamp of seminario de S. Jose
Keywords: Good

Bibliotheca, Canonica Iuridica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Bibliotheca, Canonica Iuridica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Curso de Misiones Apostolicas, Platicas Instructivas - Gual, Pedro (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Commentarius in Libros Samuelis seu I et II Regum - Hummelauer, Francisco de (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Caminho da Perfeicao - Jesus, Theresa de (Typographia Elzeviriana, 1886)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Repertorio Alphabetico e Chronologico Ou Indice Remissivo Da Legislacao Ultramarina - Joao Jose Da Silva (Typographia do Seminario de S. José, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Commentarius in Librum Iob - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Commentarius in Prophetas Minores - Knabenbauer, Iosepho (Sumptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Cursus Scripturae Sacrae, Commentarius in Rophetas Minores - Knabenbauer, Iosepho (Summptibus P. Lethielleux, Editoris, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Platicas Morales para Todos Los Domingos del Ano - Lastiesas, D. Ramon (Libreria Religiosa, Calle de Avino, Num. 20, 1886)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Thesouro do Sacerdote - Mach, Jose (Livraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Thesouro do Sacerdote - Mach, Jose (Livraria Internacional de Ernesto Chardron, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Congregacoes da Immaculada Viregem Maria E de S. Luiz Gonzaga - P. Antonio Maria Alves (Seminario De S. Jose, 1886)
Decorridos apenas poucos mees depois da minha chegada a Zi-ka-wei, em 1895.senti-me docemente impellido a proseguir na ideia, que antes tivera, de indagar os principios das Congregações de N. Senhora no imperio florido, e ligar depois os tempos antigos aos modernos, mostrando os sazonados fructos de bencão, que ellas produziram sempre, nestas remotas paragens. A empreza que, em Macau, se me afigurara impossivel por escassez de documentos, pareceu-me então de facil alcance, vendo-me em meio de uma grande bibliothca, fornecida de livros selectos. Dei-me, pois, ao trabalho de folhear alguns, e em breve, junctei uns dadosinhos preciosos, que começo hoje, meus amados Congregados, a apresentar-vos, em toda a sua simmplicidade. Possam elles despertar, em vossos coraçõesjuvenis, novos brios e alentos no amor para com a Mãe celeste, pela practica das Regras da Congregaçao a qual tendes a dita de pertencer
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Travel

Historia Sagrada do Antigo e novo Testamento - Roquete, J. I (Guillard, Aillaud, 1886)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Manuel technique d'anatomie végétale; guide pour l'étude de la botanique microscopique - Strasburger, Eduard (F. Savy, 1886)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Microscope and microscopy Technique; Microscopie Technique; Microscopy Technique; Plant anatomy; Plantes Anatomie

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry, Latin; Poésie élogieuse latine; languages

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1886)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry, Latin; Poésie élogieuse latine; languages